2012
DOI: 10.1145/2382570.2382575
|View full text |Cite
|
Sign up to set email alerts
|

Axiomatization of Socio-Economic Principles for Self-Organizing Institutions

Abstract: We address the problem of engineering self-organizing electronic institutions for resource allocation in open, embedded, and resource-constrained systems. In such systems, there is decentralized control, competition for resources and an expectation of both intentional and unintentional errors. The "optimal" distribution of resources is then less important than the endurance of the distribution mechanism. Under these circumstances, we propose to model resource allocation as a common-pool resource management pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 45 publications
0
51
0
Order By: Relevance
“…Agents take what they desire, and adapt their demand based on what they can get away with appropriating. Here, the early agents learn that they can take as much as they desire, and according to the demand adaptation mechanism (adopted from Pitt et al [1]) soon realise they can appropriate the entire pool. Finally, the first agent adapts to take everything, and all others are left with zero; the Gini coefficient is approaching 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Agents take what they desire, and adapt their demand based on what they can get away with appropriating. Here, the early agents learn that they can take as much as they desire, and according to the demand adaptation mechanism (adopted from Pitt et al [1]) soon realise they can appropriate the entire pool. Finally, the first agent adapts to take everything, and all others are left with zero; the Gini coefficient is approaching 1.…”
Section: Resultsmentioning
confidence: 99%
“…We consider the case when resources are exogenous, i.e., they are provided by the environment over time. An example of this is agents appropriating water for their needs, from a reservoir [1]. The collective task facing the agents is to allocate this resource among them.…”
Section: Problem Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…In EC we formalise these powers as fluents which indicate whether an agent has or had a specific power at a time. Pitt et al (2012) demonstrated that six of Ostrom's principles could be axiomatised for a resource-allocation problem. There are several differences between this problem and our provision and appropriation system.…”
Section: The Ec and Institutionalised Powermentioning
confidence: 99%